Identification of a mutation in a Vietnamese family with Emery-Dreifuss Muscular Dystrophy using whole exome sequencing - Thuy Duong, Nguyen; Huong Thao, Dinh; Thi Thao, Nguyen; Van Anh, Pham; Noriko, Miyake; Naomichi, Matsumoto; Van Hai, Nong (Academia Journal of Biology, 2022)
Emery-Dreifuss muscular dystrophy (EDMD) is a degenerative neuromuscular disease associated with at least nine genes, including EMD, LMNA, FHL1, TMEM43, SUN1, SUN2, TTN, SYNE1, and SYNE2. Herein, we identified a heterozygous missense LMNA mutation (NM_170707.4: c.1357C>T,p.R453W) in three members of a Vietnamese family using whole-exome sequencing (WES), in which the proband was an 11-year-old girl presenting humeroperoneal muscle weaknesses and generalized contracture. Her father and one other relative also exhibited multiple signs of muscular atrophy and contracture. Sanger sequencing in the extended family verified the causative nature of this mutation, establishing a confirmed diagnosis of autosomal dominant Emery-Dreifuss muscular dystrophy (EDMD2). The clinical presentations of each patient in this study are different from each other, demonstrating the intrafamilial phenotypic variability of this mutation. Early identification of the underlying genetic course of the disease by sequencing, combined with clinical findings provides solid evidence to diagnosis process, genetic counseling and management strategy.